Conditions. -- Vol. 1, No. 1 (1977) - . --. (Brooklyn, N.Y. Conditions, 1977)
Quarterly
v.5. The black women's issue
"A magazine of writing by women with an emphasis on writing by lesbians.
Keywords: American literature -- Women authors; American literature -- 20th century; Lesbianism